Analisis Kelurusan Sesar di Daerah Istimewa Yogyakarta Berdasarkan Data Anomali Gravitasi - Iswanudin Iswanudin; Muchamad Aryono Adhi; Muhamad Syrojudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This research aimed to analyze fault lineament patterns based on gravity anomaly data in the Yogyakarta region. The method used is the gravity method. Primary gravity data from BMKG measurements in Bantul Regency, Yogyakarta City, and Sleman Regency were processed to produce a Complete Bouguer Anomaly Map. The data were analyzed using regional-residual anomaly separation, as well as First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) techniques to clarify geological structure boundaries. The results showed that the complete Bouguer anomaly distribution ranges from 56.06 mGal to 130.38 mGal. Derivative analysis successfully identified two main fault structures: the Opak Fault in the southern part with a southwest-northeast direction spanning approximately 44.8 km, and the Mataram Fault in the northern part with a west-east direction spanning approximately 27.2 km. There is a good correlation between high gravity anomalies and high Vs30 values, which indicates compact rocks and more stable soil conditions against earthquake shocks, and vice versa. In conclusion, two main fault structures were identified in the research area, namely the Opak Fault in the south with a southwest-northeast direction and the Mataram Fault in the north with a west-east direction. Keywords: Gravity Anomaly, Earthquake Shock, Fault